Development of Community-based Disaster Management Models in Nakhon Chai Burin - Laokhompruttajarn, Thitirat; Laokhompruttajarn, Jiratchaya (Dhammathas Academic Journal, 2023)
The purposes of this research were 1) to study the problems and impacts of disasters, 2) to study disaster management, 3) to develop the disaster management model, and 4) to propose policy recommendations on community-based disaster management in the Nakhon Chai Burin. This was mixed-method research. The sample included 439 people and 48 key informants from the municipality in Nakhon Chai Burin District. Data were collected through a questionnaire, in-depth interviews, and focus group discussions and analyzed by number, percentage, mean, standard deviation, and content analysis. The research result finds that: 1. The overall problems and impacts of the disaster were at a high level ( = 4.14, S.D. = 0.18). 2. The overall disaster management was at a high level ( = 3.56, S.D. = 0.30). Preparation before the disaster was at a high level ( = 4.33, S.D. = 0.18). Management during the disaster was at a high level ( = 3.82, S.D. = 0.28), and restoration after the disaster was at a moderate level ( = 3.00, S.D. = 0.30). 3. For a community-based disaster management model, it was found that 1) preparation by planning an adequate budget for management raised awareness, provided knowledge, and regularly practiced based on guidelines. 2) Disaster management was based on an efficient system. 3) Restoration was performed through repair, renovation, and psychological care for victims. 4. Policy recommendations for disaster management included 1) providing necessary manpower and equipment for disaster management, 2) preparing community-based guidelines, 3) building awareness of the disasters in all sectors, and 4) effectively coordinating with network partners.